ANALISA KELAYAKAN BISNIS PROYEK PEMBANGKIT LISTRIK TENAGA ANGIN (PLTB) DI INDONESIA DENGAN MENGUNAKAN SOFTWARE RETSCREEN - Muhammad Nashar (Jurnal Ilmiah Manajemen dan Bisnis, 2015)
Business feasibility analysis of systematic and rational is necessary before a project is needed before investment activity is realized. A tool is a software that can simplify the calculation of a project feasibility analysis is useful to simplify and make more accurate calculation can. Planned development projects Wind Power Generation (thermal power station) in Indonsia business is still something very new and still not widely practiced by investors. Indonesia has the potential of wind energy has been measured around 9.2 GW by the utilization is still very small, only about 1mW. It is thus very good potential of wind energy to be utilized. Business feasibility of simulation calculations using the software Retscreen Ambon in Maluku province, the area for projects with installed generating capacity of 330kw or a total of 5 x 1650 Kw obtained. NPV Value: USD 2,197,870 with pre-tax equity IRR of 28.8% for the IRR before tax as 14.3% for equity IRR after tax is 25.9% and for the post-tax IRR of 12.8% was also obtained assets payback period 5, 5 years. With the look of the above calculation, the electric power plant project Bayu (thermal power station) is a project that deserves to be investment Keywords: Business Feasibility Analysis, thermal power station, RetScreen